The taxonomy and life history of the blue stingray, Dasyatis marmorata capensis (Batoidea : Dasyatidae) from Southern Africa - Cowley, Paul D (Paul Denfer), 1964- (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1990)
The blue stingray, Dasyatis marmorata capensis is an important recreational shore angling species, especially amongst tournament anglers, in South Africa. The taxonomy and aspects of the biology of this species were investigated from specimens collected between March 1987 and May 1989, from various localities along the southern African coastline. Morphological comparisons were made between Dasyatis pastinaca, Dasyatis marmorata and the local variety. The results indicated that the local variety is different to D. pastinaca in colouration, disc length size, and vertebral and radial counts. The proposed new sub-species Dasyatis marmorata capensis is closest to Dasyatis marmorata of the north-eastern Atlantic coast, but differs in snout angle, disc length and snout to vent length. Analysis of catch per unit of effort data revealed that the blue stingray exhibits distinct seasonality. Adult and sub-adult fish undertake an annual onshore/offshore migration and invade the inshore region between spring and summer, while juveniles remain offshore and utilize this zone as a nursery area. Length-at-age and growth rates for both sexes were estimated from bands formed seasonally in the vertebral centra. The derived von Bertalanffy growth parameters indicated that females reach a greater asymptotic size (913.8 mm DW) and have a slower growth rate (K = -0.07) than males (531.8 mm DW, K = -0.17). Growth rates of juvenile captive specimens compared favourably with back calculated values, at approximately 65 mm/year, for the first year of growth. Dasyatis marmorata capensis is an aplacental viviparous elasmobranch with a well defined annual breeding cycle. Young are released , at a size of 170-200 mm DW, from October to December after a gestation period of approximately nine months. An average fecundity of 3.07 was calculated . Examination of gonadal development indicated that sexual maturity is first attained at a size of 408 and 500 mm DW in males and females, respectively, corresponding to ages 4.5 and 7 years. Size-related food habits were determined independently from three depth zones. The major prey items for each size class were directly related to the abundance of the infauna of the different depth zones. Polychaeta, amphipoda and stomatopoda were the major prey items in the offshore zone. In the nearshore zone, the dominant prey species were Balanoglossus capensis and Callianassa spp .. The high incidence of empty stomachs and the presence of prey items which occur in greatest abundance beyond the surf zone indicated that this zone is not utilized for the purposes of feeding.
Keywords: Stingrays -- Africa, Southern; Dasyatidae